Interaksi Indepedensi, Pengalaman, Pengetahuan, Due Professional Care, Akuntabilitas dan Kepuasan Kerja Terhadap Kualitas Audit - Melody Iskandar; Stefani Lily Indarto (Jurnal Ekonomi dan Bisnis, 2015)
This study aims to determine whether job satisfaction influences the relationship between the independence, experience, knowledge, due care professionals, and accountability on audit quality among auditor who worked at public accounting firms in Semarang. The examination results should be able to present accountability and assessment toward fairness of the financial statements, as well as the appropriateness of the financial information with the criteria or rules that have been set. The auditor is expected to carry out the audit properly and resolve any audit process steps, and considering the sufficient audit evidence discovered to ensure the audit quality. The population comprises auditors who work at public accountant firms in Semarang. This research uses 45 auditors as samples. The data is processed using multiple regressions to analyze the relationship between the dependent and independent variables. The results of this study indicate that job satisfaction affects only the relationship between independency and accountability on audit quality. While job satisfaction does not affect the relationship between the due professional care, experience and knowledge to audit quality.